Peran Dinas Koperasi dan UKM dalam Pengelolaan Pasar Tradisional di Padang Kaduduak Kota Payakumbuh - Jhordy Fernando; Jumiati Jumiati (Policy, Law and Political Research Center, 2022)
The purpose of this paper is to describe the findings related to the role of cooperatives and the SME sector in the management of traditional markets in Padang Kaduduak Payakumbuh City. The methods used in this study are qualitative and descriptive. Therefore, the research informant is the target sample. Data collection techniques are carried out through interviews, observations and literature reviews, and of data presentation so that accurate conclusions can be drawn from the data. The findings suggest that the role of cooperatives and SMEs in managing traditional markets in Padang Kaduduk Payakumbuh is still missing, and the public still lacks interest in shopping at traditional markets.